2022
DOI: 10.3389/fpubh.2022.890604
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events and Chronic Fatigue Among Chinese Government Employees: A Population-Based Cohort Study

Abstract: BackgroundCurrently, evidence on the role of stressful life events in fatigue among the Chinese working adults is lacking. This study aimed at exploring the prospective associations between stressful life events and chronic fatigue among Chinese government employees.MethodsFrom January 2018 to December 2019, a total of 16206 government employees were included at baseline and they were followed-up until May 2021. A digital self-reported questionnaire platform was established to collect information on participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Concerning cumulative fatigue, 47% of the respondents had symptoms of cumulative fatigue, and 22.7% of the total participants had serious symptoms of cumulative fatigue. This index was also higher than the average level of other industries [ 28 , 29 , 30 ]. Stress and fatigue might have some correlation.…”
Section: Discussionmentioning
confidence: 84%
“…Concerning cumulative fatigue, 47% of the respondents had symptoms of cumulative fatigue, and 22.7% of the total participants had serious symptoms of cumulative fatigue. This index was also higher than the average level of other industries [ 28 , 29 , 30 ]. Stress and fatigue might have some correlation.…”
Section: Discussionmentioning
confidence: 84%
“…All employees filled out an online questionnaire via a cellphone or tablet prior to the ultrasound examination. Detailed information and data collection procedures have been published in previous studies [ 17 , 18 ]. We excluded participants who had a previous history of chronic hepatitis, cirrhosis, liver cancer ( N = 73) or excessive alcohol consumption (Males: ≥25 g per day; females: ≥15 g per day) ( N = 295).…”
Section: Methodsmentioning
confidence: 99%
“…Stressful life events of Chinese government employees were assessed using the Life Events Scale (LES), the details of which were described in our previous study [17]. There are 48 items in this scale, which were classified into different dimensions, including stressful life events related to marriage and family, stressful life events related to work and study, health-related events, stressful life events related to accidents, legal disputes, and economic problems.…”
Section: Stressful Life Eventsmentioning
confidence: 99%
“…Based on participants' daily experiences over the past year, Chinese government employees were asked to choose "yes" or "no" for each item. In the current study, the Chinese version of the Life Events Scale was used, for which our previous study reported favorable validity and reliability and which is widely used in China [17]. In this study, we divided stressful life events into four groups according to the number of occurrences: none, one, two, and three or more stressful life events.…”
Section: Stressful Life Eventsmentioning
confidence: 99%